2014
DOI: 10.1080/19371918.2014.888533
|View full text |Cite
|
Sign up to set email alerts
|

Current Approaches to Support the Psychosocial Care of African American Adults with Diabetes: A Brief Review

Abstract: African Americans are disproportionately affected by type 2 diabetes and experience significantly higher age-adjusted prevalence of the disease. Psychosocial support, material resources, and education can have a significant impact on successful diabetes management, particularly among populations with diabetes-related psychological distress such as African Americans. This brief review of the literature identifies and synthesizes current evidence on faith-based, community-based, empowerment-based, strength-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, subsequent research demonstrated that knowledge alone was not enough to stimulate important behavior changes among patients with diabetes, highlighting a need for a more comprehensive approach with continuous and repetitive interactions, and focusing on other important outcome variables, such as behavioral, social, and psychological factors [9] , [21] . An emphasis on incorporating issues of self-efficacy, problem-solving abilities, and skills-building in program success was therefore introduced [8] , [13] , and a shift toward more participatory, interactive interventions developed, focusing on strategies targeting lifestyle changes, patient motivation and personal attitudes toward the chronic condition [22] , [23] , [24] . Adopting a participatory approach demonstrated better understanding and reinforcement of educational messages through the patient’s involvement in different group activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent research demonstrated that knowledge alone was not enough to stimulate important behavior changes among patients with diabetes, highlighting a need for a more comprehensive approach with continuous and repetitive interactions, and focusing on other important outcome variables, such as behavioral, social, and psychological factors [9] , [21] . An emphasis on incorporating issues of self-efficacy, problem-solving abilities, and skills-building in program success was therefore introduced [8] , [13] , and a shift toward more participatory, interactive interventions developed, focusing on strategies targeting lifestyle changes, patient motivation and personal attitudes toward the chronic condition [22] , [23] , [24] . Adopting a participatory approach demonstrated better understanding and reinforcement of educational messages through the patient’s involvement in different group activities.…”
Section: Discussionmentioning
confidence: 99%
“…These focused health interventions are important for minority populations because much of the evidence in prior health intervention studies has its roots in populations of European origin from developed nations [ 12 , 13 ]. When factoring in psychosocial support for African American healthcare issues, studies have described faith-related, community-related, empowerment-related, and culturally appropriate intervention strategies [ 14 ]. A systematic literature review in 2015 by Smalls et al assessed that community-based interventions generally led to significant reductions in glycosylated hemoglobin (A1c) levels in African Americans with type 2 diabetes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, adults in later life with comorbid depression and diabetes are less likely to adhere to medication, exercise and diet regimens and are more likely to experience reductions in quality of life and increased medical expenditures [ 8 ]. Considering the increased risk for depression among older adults with diabetes, the treatment of depression is critical to achieving optimal health [ 9 ]. However, mental health status is often overlooked in health care settings as a common comorbidity alongside chronic diseases such as diabetes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%